Photocatalytic TiO2 films and membranes for the development of efficient wastewater treatment and reuse systems - Choi, Hyeok; Antoniou, Maria G.; De La Cruz, Armah A.; Stathatos, Elias; Dionysiou, Dionysios D. (My University, 2007)
In order to develop efficient photocatalytic TiO2 films and membranes for application in water and wastewater treatment and reuse systems, there is a great need to tailor-design the structural properties of TiO2 material and enhance its photocatalytic activity. Through a simple sol-gel route, employing self-assembled surfactant molecules as pore directing agents along with acetic acid-based sol-gel route, we have fabricated nanostructured crystalline TiO2 thin films and TiO2/Al2O3 composite membranes with simultaneous photocatalytic, disinfection, separation, and anti-biofouling properties. The highly porous TiO2 material exhibited high specific surface area and porosity, narrow pore size distribution, homogeneity without cracks and pinholes, active anatase crystal phase, and small crystallite size. These TiO2 materials were highly efficient in the decomposition of methylene blue dye and creatinine, destruction of biological toxins (microcystin-LR), and inactivation of pathogenic microorganisms (Escherichia coli). Moreover, the photocatalytic TiO2 membranes exhibited not only high water permeability and sharp polyethylene glycol retention but also less adsorption fouling tendency. Here, we report results on the synthesis, characterization, and environmental application and implication of photocatalytic TiO2 films and membranes.
Keywords: TiO2; Photocatalysis; Membrane; Thin film; Advanced oxidation technologies; Sol-gel; Antibiofouling; Biological toxins; Microbial inactivation; Water and wastewater treatment